Conflict between Texts: Causes and Prevention - Almujahed, Muhammad Said; Hammad , Ziad Abu (Dirasat: Shari’a and Law Sciences, 2020)
The study aims to clarify the idea of conflict between texts, its causes and how to deal with conflicts between texts. The study touched on the meaning of the conflict, linguistically and idiomatically, the causes of the conflict, and how to eliminate it. The inductive-analytical approach was used by extrapolating the possible causes of conflicts between texts, analyzing them, and then revealing the way of understanding them. The analysis was supported with examples of verses and hadiths. The study concluded that the most comprehensive definition of the conflict among the fundamentalists is the contrast between the legal evidence. The study also concluded that there are several reasons for the conflict, the most important of which are: change of provision and diversity in provision. It also concluded that the two provisions differed because the two cases differed, so that each text was applied out on a specific case. It also found that conflict is treated in various ways, such as copying, combining, or weighting if each is not possible.